“Duración e intensidad de la latencia de semillas de arroz (oryza sativa L.) bajo condiciones de labotario en Tarapoto-San Martín” - Tirado Ramírez, Henry Luis (2006)
This research work was to determine the effect of drying (natural and artificial) and stored (standby) on the breaking of dormancy, thus obtaining seeds with high germination and high percentage of germination energy in shortest time. Was carried out in the facilities of the Regional Committee of seeds of San Martin, located in the city of Tarapoto to 6 ° 30' 00 "South latitude, 76° 29'00" West longitude at an altitude of 330 m, s, n, m. Is applied the DCA with them arrangements factorial of 7 by 2 by 7 and 7 by 1 or, with three tests by treatment, them seeds of varieties and lines have been collected of different fields of farmers in the area commercial in the area of low Mayo (Cacatachi) and of the high Mayo (the conquest-Moyobamba). The results reported that higher germination averages were with linea26, linea14, Moro and Alto Mayo with averages of 97,95%, 96,19%, 96,09% and 87,62%; the factor obtained types of drying may...